IMPLEMENTASI KEBIJAKAN TUNJANGAN KHUSUS GURU DAERAH TERPENCIL DI DESA BATURUBE KECAMATAN BUNGKU UTARA KABUPATEN MOROWALI - Taruangi, Hetrisia Fatri (Katalogis, 2014)
The purpose of this study is to determine the Implementation of teacher distinctive grantpolicy in the remote area of Baturube Village north Bungku Sub-district Morowali, throught the implementation of the theory of Edward III which includes communication, resources, disposition and bureaucratic structure. The research method used is descriptive qualitative helped by six informants where they were selected by way of purposive. The method of collecting data was through observation, interviews and documentation, with the data analysis techniques include data reduction, data display, drawing conclusions and verification of data. The result of the research explain that the implementation of teacher distinctive grant policy in the remote area of Baturube village North Bungku Sub-district Morowali not going well yet, this can be seen from the implementation obstacle in aspect of communication and resource such as lack of socialization carried, the inadequeta of human resource capacity, lack of facilities, supporting infrastructure, and limited funding, as of disposition aspects although the implementers respond and support the implementation of this program however in practice there are certain weaknesses that need to be anticipated and addressed wisely, and from the aspect of bureaucratic structure also shows that even though this policy has been equipped with the rules, but the implementation is not going well due to lack of understanding and knowing executing tasks to be done.